2003
DOI: 10.1007/s00424-002-0943-5
|View full text |Cite
|
Sign up to set email alerts
|

UCP3 protein expression is lower in type I, IIa and IIx muscle fiber types of endurance-trained compared to untrained subjects

Abstract: Uncoupling protein 3 (UCP3) is a muscle mitochondrial protein believed to uncouple the respiratory chain, producing heat and reducing aerobic ATP production. Our aim was to quantify and compare the UCP3 protein levels in type I, IIa and IIx skeletal muscle fibers of endurance-trained (Tr) and healthy untrained (UTr) individuals. UCP3 protein content was quantified using Western blot and immunofluorescence. Skeletal muscle fiber type was determined by both an enzymatic ATPase stain and immunofluorescence. UCP3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 44 publications
(54 reference statements)
6
71
3
Order By: Relevance
“…Recent studies indicate that mitochondria from different fiber types may have different metabolic characteristics. This includes a higher UCP3 content in type 2X fibers in human skeletal muscle (46) and a lower lipid oxidative capacity per mitochondria and higher hydrogen peroxide production in type 2 fibers from rodent muscle (27,47). Correspondingly, we observed a positive association between the proportion of type 1 fibers and mitochondrial respiration with palmitoyl-L-carnitine plus malate and a correlation between type 2X fibers and noncoupled (state 4) respiration.…”
Section: Discussionsupporting
confidence: 56%
“…Recent studies indicate that mitochondria from different fiber types may have different metabolic characteristics. This includes a higher UCP3 content in type 2X fibers in human skeletal muscle (46) and a lower lipid oxidative capacity per mitochondria and higher hydrogen peroxide production in type 2 fibers from rodent muscle (27,47). Correspondingly, we observed a positive association between the proportion of type 1 fibers and mitochondrial respiration with palmitoyl-L-carnitine plus malate and a correlation between type 2X fibers and noncoupled (state 4) respiration.…”
Section: Discussionsupporting
confidence: 56%
“…Immunofluorescence. Immunfluorescence experiments were performed as reported previously (25). The PGC-1 (sc-5816; Santa Cruz Biotechnologies, San Diego, CA) and PPAR-␣ (Dr. David Bell, The University of Nottingham, U.K.) antibodies, respectively, were diluted 1:200 and 1:500 in PBS containing 0.5% BSA and 0.1% NaN 3 and were visualized separately, using a donkey sense CAT GTG GCA GAA GCA CTA TGT GT 80 60 anti GCC ACC CAC TCT TTG TCA AAG ␤-Actin sense ACT GAC TAC CTC ATG AAG AT 535 56 anti CGT CAT ACT CCT GCT TGC TGA T anti-goat (IgG) and a goat anti-mouse (IgG) antibody, both conjugated with Alexa Fluor 594 (Molecular Probes Europe, Leiden, the Netherlands) at a concentration of 1:500, for 60 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, UCP3 is upregulated under conditions of an abundance of fatty acid supply to the mitochondria, such as during fasting (37), high FFA levels (38), acute exercise (39), and high-fat feeding (36,38). On the other hand, downregulation of UCP3 occurs when fatty acid oxidation is increased or plasma FFA levels are lowered, such as with endurance training (40,41) and weight reduction (42). In addition, we recently reported that UCP3 protein content is inversely related to fat oxidative capacity of muscle, indicating an increased need for UCP3 in those muscles with a low-fat oxidative capacity (43).…”
Section: Mitochondrial Damage: a Role For Lipid Peroxides?mentioning
confidence: 99%
“…Thus, the normal physiological response to physical inactivity and/or a low oxidative capacity is an upregulation, not a downregulation, of UCP3. Endurancetrained athletes with a high oxidative capacity are characterized by very low levels of UCP3 when compared with untrained subjects (41). In addition, UCP3 protein levels are highest in muscles with a low oxidative capacity (43).…”
Section: Mitochondrial Damage: a Role For Lipid Peroxides?mentioning
confidence: 99%